Core/shell microrod arrays of NiO/Co-Fe layered double hydroxides deposited on nickel foam for energy storage and conversion. (20th January 2017) - Ma, KeYuan; Liu, Fu; Zhang, MeiBian; Zhang, XiaoBin; Cheng, J.P.
Highlights: Co-Fe LDH@NiOcompositewithshell-corestructurewasdepositedonNifoam. The shell-core structure will generate high resistance between the interface of core and shell. Electrochemical performance of the hybrid was improved at a low current density. Abstract: Hybrid materials with three-dimensional hierarchical architectures have drawn considerable attention in the field of energy storage and conversion owing to the improved electrolyte-accessible surface area and shortened ion transfer paths. In this work, a novel hierarchical Co-Fe LDH@NiO composite with shell-core rod arrays grown on the surface of Ni foam is presented for the use of electrode material without any organic binders and conductive agents. It is found that the expected good conductivity, large electrolyte-accessible surface area and sufficient active sites cannot be well achieved at the same time. Owing to the facile electrolyte diffusion paths and large exposed surface area, Co-Fe LDH@NiO with 46.06% Co-Fe LDH has a specific capacity of 361 C g −1 at 1 A g −1 . However, at high current densities, its performance decreases quite dramatically due to the poor electrical conductivity of NiO support and the high interface contact resistance between NiO microrods and Co-Fe LDH nanosheets. The assembled hybrid supercapacitor based on Co-Fe LDH@NiO- Ni and activated carbon electrodes can deliver an energy density of 22 Wh kg −1 at the power density of 800 W kg −1, showing a promising potential in energy storage and conversion.